Soviet as personal: About Mikhail Elizarov’s song “Mr. Main Wind” - Olesya R. Temirshina (RUDN Journal of Studies in Literature and Journalism)
The article represents an interpretation of M. Elizarov’s song “Mr. Main Wind”. It is shown that the Soviet cultural code forms a ‘double’ lyrical and historical ‘narrative’ of this song. On a superficial level, the text presents the plot of collapse of the USSR; on a deep level, the historical narrative encodes the personal drama of the lyrical subject. A linguistic analysis of deictic structure of the song made it possible to determine mechanisms of formation of this plot. It was shown that the deictic ‘configuration’ identified in the analyzed song is also present in other poetic texts of Elizarov, that allows us to talk about its plotgenerating potential. It has been proven that the identification of personal catastrophe and historical drama turns out to be the ‘topos’ of Elizarov’s poetics as a whole. The interference of these lines at the psychological level is apparently ensured by a common emotional field of experience, within which both events are endowed with high emotional and personal significance. This leads to the complexity of the interaction between the spheres of the personal and public: the ‘floating’ point of reception leads to difficulty of determining the dominant line of meaning, because the personal is ‘hidden’ in the public, and the public is ‘encrypted’ by the personal. All this makes it possible to significantly correct the current idea of Elizarov’s work as postmodern and to discover other sources of his creative method related to the poetics of Mayakovsky.